A Critical Review of Metaphor - Ramin Golshaie (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article presents a critical review of the Farsi translation of the book Metaphor authored by David Punter. The book was translated into Farsi by Mohammad Mehdi Moghimizadeh and published by Elm publications. In this book, Punter explores the role of metaphor in different aspects of human knowledge, from literature, philosophy, and religion to politics and psychoanalysis. The translated version of the book was evaluated in terms of both form and content. Form evaluation included technical, organizational and editorial characteristics of the book, and content evaluation assessed the quality and accuracy of translation and equivalents. Including a section titled “Translator’s endnotes” in the translated version, footnoting technical terms and proper names, and fluent language are among the merits of the book. On the other hand, the existence of typographical errors, use of inaccurate equivalents, inconsistent use of equivalents, insufficient command of the source language grammar, and distortion of metaphors during the process of translation are the drawbacks of the book. The book has the potential to open up new horizons to Farsi readership, especially for those who have a background within the domain of metaphor and critical studies. A better understanding of examples and metaphors discussed, however, would require the readers to refer back to the original version of the book.